Factor Affecting Liquidity of Commercial Banks in Indonesia - Hartanto, Evan; Dewi, Vera Intanie; Halim, Budi Tjahja (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Banks need to maintain soundness levels, one of which is the level of liquidity. Bank liquidity will be tested in the case of â€œBank Runsâ€, which occurred frequently both in Indonesia and in the world. The main purpose of this study is to develop an understanding of factors that affect liquidity in the banking sector with a focus on bank groups that belong to the category of Bank Group based on Core Capital (KBMI) 4. This study was explanatory research. Data were collected using the documentation method from the financial data of KBMI 4 banks. The sample for this study consisted of 4 banks. The results of the study showed that NPL had a negative effect on LDR and NWC had a positive effect on LDR, while CAR did not affect LDR.